Ethanolic Extract of Fingerroot (Boesenbergia pandurata Roxb.) Rhizomes exhibits Analgesic and Anti-Inflammatory Activities in Swiss Webster Mice - Yuniarto, Ari; Setiawan, Abdul Aziz; Asyila, Nadia Dinda (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Pain is a sensory response that indicates tissue damage caused by mechanical, chemical, or physical stimuli. This study aimed to evaluate the analgesic and anti-inflammatory activities of the ethanol extract of fingerroot rhizomes (EEFR) in mice. The extract was prepared by maceration using ethanol and tested in mice divided into five groups: three treatment groups receiving EEFR at doses of 100, 200, and 400 mg/kgBW, a positive control group, and a negative control group. Analgesic activity was assessed by the number of writhing responses induced by 1% acetic acid, while anti-inflammatory activity was evaluated based on paw edema induced by 1% carrageenan. The results showed that EEFR at a dose of 400 mg/kgBW produced the most significant analgesic and anti-inflammatory effects, with pain protection and inflammation inhibition percentages of 69.81% and 58.97%, respectively. These findings indicate that EEFR has potential as a natural analgesic and anti-inflammatory agent.